Mental illness and a high‐risk, elderly Japanese population: characteristic differences related to gender and residential location. Issue 4 (28th October 2013) - Kikuchi, Hiroyuki; Takamiya, Tomoko; Odagiri, Yuko; Ohya, Yumiko; Shimomitsu, Teruichi; Inoue, Shigeru
Abstract Purpose Examining the sociodemographic determinants of psychological distress is important in identifying specific subgroups in need of further intervention. However, there are few studies focusing on older populations and on the role of gender or location of residence. To try to clarify characteristics of a population at high risk for mental illness, we examined the sociodemographic determinants of psychological distress in older adults living in three different locations. Methods A mail survey was used to collect data on levels of psychological distress and sociodemographic characteristics from a population‐based sample of 1894 older adults who lived in Bunkyo (urban setting), Fuchu (suburban setting) and Oyama (rural setting) in Japan (aged 65–74 years, 51.3% men). Psychological distress level was measured based on Kessler's six‐item psychological distress scale (K6) and dichotomized into two groups with a cut‐off score of 5 (0–4 or 5–24). Multiple logistic regression analyses were used to examine the associations between sociodemographic factors, specifically gender and location of residence, and psychological distress levels. Results The variables of older age, living in Bunkyo, living in Oyama and living alone were significantly associated with high psychological distress. Although these associations were observed in men, no associations were observed in women. Location‐specific analyses showed significant associations between sociodemographic and psychological distress among men living in Oyama, but not among those in Bunkyo or Fuchu. Conclusions Sociodemographic factors were significantly correlated with psychological distress, particularly among older men in rural areas. Characteristics of a population at high risk for mental illness may vary based on gender and location of residence. Health promotion initiatives for older adults may be more effective if they take these demographic factors into account.